PENGARUH MAKRO EKONOMI TERHADAP INDEKS HARGA SAHAM EMPAT NEGARA DI ASIA TENGGARA PERIODE 2003-2013 - Anesa Novtiani Saragih; Koramen H. Sirait (Media Ekonomi, 2015)
Investment in capital investment which is excessively done by companies or individuals in countries Southeast Asia. Investment which typically done is an investment in the capital market. By investing in these capital markets, it can raise particular country’s economic activity where share is one of the instruments of capital market. Many investors prefer this instrument in investing due to the attractive shares advantage. The movement of share prices changes every day, and observing the movements is essential by the investors. The information that can be observed by the investors in observing the movements of share prices is the joint share price index in a country. This research aims to analyze influence the macroeconomic variables towards share price index in some Southeast Asia countries, namely Indonesia, Malaysia, Philippines and Singapore from 2003 to 2013. This research employs panel data analysis to determine the variables which affect share prices in four Southeast Asian countries. The variables that affect the share price index are the interest rate, IHK, and GDP. Based on the panel data analysis, it is shown that the interest rate gives negative effect and significant towards the share price index of four countries in Southeast Asia, IHK gives negative effect and not significant towards the share price index of countries in Southeast Asia, and GDP gives positive effect and not significant towards the share price index of countries in Southeast Asia.